ANALIIS SPASIAL KONVERSI LAHAN SAWAH DI KABUPATEN BEKASI (STUDI KASUS DI KECAMATAN CIBITUNG DAN TAMBUN) - Dede Dirgahayu (Jurnal Penginderaan Jauh dan Pengolahan Data Citra Digital, 2004)
The result of spatial analysis indicates that there has been position sidetrack of paddy field concentration (SM=Spatial Mean)from the year 1996 until the year 2000 to the North East direction as far as 691 m in Cibitung district and 481 m in Tambun district. The SM movement is away from the center of social economic activity of the community whether in yhe local area (district) or the regional area (City, Regency). Land conversion of paddy field into non-agricultural land that mostly occur are as a residential and industrial area. Land conversion has also occured in Tambun of paddy - then more settlement type about 105.2 Ha and 154.6 Ha in Cibitung. Land conversion of paddy - then more industry type has occured in Cibitung about 486.1 Ha and 87.9 Ha in Tambun. Paddy field conversion that occurs in the research location has taken place in Highly Suitable (S1) land, and has high productivity because it taken place in the area High Accessibility towards main road and center of the district.